Prevalence of tobacco smoking and measures preventing tobacco smoke inhalation among third grade secondary school students in Bialystok - Kanicka, Magdalena; Szpak, Andrzej; Karpińska, Maria (Polish Journal of Public Health, 2010)
Introduction. Tobacco smoking poses a serious health risk. Inhalation of tobacco smoke by young people is determined by various factors, including their school’s smoking policy, examples set by school staff, health education and other measures undertaken to prevent smoking in schools. Aim. To investigate the prevalence of smoking among secondary school students, adherence to school smoking control policy by youth and adults, and the assessment of health education on reducing the prevalence of smoking. Material and method. The survey was conducted in May 2009 and included 685 third grade students from 8 randomly selected secondary schools in Bialystok. Results. In the study group, 71.7% of the students stated that they did not smoke even one cigarette within the studied period of time and 27.7% of respondents admitted to smoking. Among the smoking students, 21.4% admitted to smoking in the school building and 32.1% admitted to smoking near their school. Sixty-three point one percent (63.1%) of the surveyed students attended school-based health education lessons on harmful effects of smoking. Conclusions. Out of all the surveyed 3rd grade students, 25% smoked cigarettes and the percentage of smoking was higher among boys than among girls. Over half of the surveyed secondary school students were exposed to passive smoking and over 60% of them said the school was a place of exposure to passive smoking.